PROGAM EKSTRAKULIKULER DRUMBAND DALAM MENINGKATKAN PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR - Ula Aulia As Sanusi; Wasis Wijayanto (Smart Education, 2026)
Abstract: Character education is an important aspect in the formation of children's attitudes and behaviors in elementary school. Drumband extracurricular activities serve as an effective tool in combining the development of musical arts skills and the cultivation of character values. The purpose of this study is to describe the implementation of extracurricular activities of drumbands and analyze their influence on the development of children's musical arts skills and character in elementary schools. This study adopts a qualitative approach with a case study method conducted at SD Negeri 1 Kedungwaru Kidul, Demak Regency. The research subjects included grade IV students, classroom teachers, and drumband coaches. Techniques for collecting data include observation, interviews, and document collection, while data validity is tested through triangulation of sources, techniques, and time. The results of the study showed that the extra drumband activities were carried out well and sustainably. Student involvement in this activity has a positive effect on the development of musical skills in the psychomotor, cognitive, and affective fields. Students can play musical instruments correctly, know the different types and purposes of musical instruments, and show an attitude of discipline, responsibility, cooperation, and confidence. In addition, drumband activities also help increase creativity and student achievement. Keywords: Extracurricular Drum Band, Character Education, Music Arts, Elementary School. Abstrak: Pendidikan karakter adalah aspek penting dalam pembentukan sikap dan perilaku anak-anak di sekolah dasar. Kegiatan ekstrakurikuler drumband berfungsi sebagai alat yang efektif dalam menggabungkan pengembangan keterampilan seni musik dan penanaman nilai-nilai karakter. Tujuan dari penelitian ini adalah untuk menggambarkan pelaksanaan kegiatan ekstrakurikuler drumband serta menganalisis pengaruhnya terhadap pengembangan keterampilan seni musik dan karakter anak-anak di sekolah dasar. Penelitian ini mengadopsi pendekatan kualitatif dengan metode studi kasus yang dilakukan di SD Negeri 1 Kedungwaru Kidul, Kabupaten Demak. Subjek penelitian meliputi siswa kelas IV, guru kelas, dan pelatih drumband. Teknik untuk mengumpulkan data mencakup observasi, wawancara, dan pengumpulan dokumen, sementara validitas data diuji melalui triangulasi sumber, teknik, dan waktu. Hasil penelitian menunjukkan bahwa kegiatan ekstra drumband dilakukan dengan baik dan berkelanjutan. Keterlibatan siswa dalam aktivitas ini memberikan efek positif pada pengembangan keterampilan musik di bidang psikomotor, kognitif, dan afektif. Siswa bisa memainkan alat musik dengan benar, mengetahui berbagai jenis serta tujuan alat musik, dan menunjukkan sikap disiplin, tanggung jawab, kerjasama, serta kepercayaan diri. Kata kunci: Sistem Informasi, Perpustakaan Digital, Website, RAD, SMK Rahmat Islamiyah Medan.